1998
DOI: 10.1002/(sici)1097-4601(1998)30:11<859::aid-kin8>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Thermal decomposition of CF3Br using Br-atom absorption

Abstract: Br-atom atomic resonance absorption spectrometry (ARAS) has been developed and applied to measure thermal decomposition rate constants for CF Br (ϩ Kr) : CF ϩ 2 (ABS) ϭ 1.410 ϫ 10 ϭ 1.419 ϫ 10 cm was then used to convert (ABS) to Br-atom profiles which were then analyzed to give measured rate constants. These can be expressed in second-order by 24488 K/T ) cm molecule s (Ϯ33%, 1222 Յ T Յ 1624 K). proach was used to rationalize the data. Theory indicates that the dissociation rates are closer to second-than to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
(32 reference statements)
2
1
0
Order By: Relevance
“…For example, the CF 3 -H bond energy of 106.4 ( 0.7 kcal/mol is in excellent agreement with the measurement of Hranisavljevic and Michael 14 of 106.3 ( 0.6 kcal/mol as well as with several older measurements. 33, [36][37][38][39] The CF 3 -Br bond dissociation energy of 70.8 ( 0.7 kcal/mol is exactly the same as the value obtained by Skorobogatov et al, 11,12 Asher and Ruscic, 6 and Hranisavljevic et al 13 and in excellent agreement with the values of 70.5 ( 1.0 kcal/mol by Tsang 4 and 71.0 ( 0.6 kcal/mol by Ferguson and Whittle. 46 The CF 3 -I bond dissociation energy of 54.3 ( 0.7 kcal/mol is identical to the determination by Asher and Ruscic 6 and in excellent agreement with the value of 54.4 ( 0.4 by Skorobogatov et al [7][8][9] The implied CF 3 -Cl bond energy of 87.3 ( 0.9 kcal/mol is in agreement, within the error bar, with the result of Kumaran et al 5 who obtained 88.4 ( 1.5 kcal/mol (87.5 ( 1.5 kcal/mol at 0 K) from Troe/Lennard-Jones and RRKM/ Gorin fits of their kinetic data and who early on suggested that the CF 3 -Cl bond energy implied by JANAF is too low.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…For example, the CF 3 -H bond energy of 106.4 ( 0.7 kcal/mol is in excellent agreement with the measurement of Hranisavljevic and Michael 14 of 106.3 ( 0.6 kcal/mol as well as with several older measurements. 33, [36][37][38][39] The CF 3 -Br bond dissociation energy of 70.8 ( 0.7 kcal/mol is exactly the same as the value obtained by Skorobogatov et al, 11,12 Asher and Ruscic, 6 and Hranisavljevic et al 13 and in excellent agreement with the values of 70.5 ( 1.0 kcal/mol by Tsang 4 and 71.0 ( 0.6 kcal/mol by Ferguson and Whittle. 46 The CF 3 -I bond dissociation energy of 54.3 ( 0.7 kcal/mol is identical to the determination by Asher and Ruscic 6 and in excellent agreement with the value of 54.4 ( 0.4 by Skorobogatov et al [7][8][9] The implied CF 3 -Cl bond energy of 87.3 ( 0.9 kcal/mol is in agreement, within the error bar, with the result of Kumaran et al 5 who obtained 88.4 ( 1.5 kcal/mol (87.5 ( 1.5 kcal/mol at 0 K) from Troe/Lennard-Jones and RRKM/ Gorin fits of their kinetic data and who early on suggested that the CF 3 -Cl bond energy implied by JANAF is too low.…”
Section: Resultssupporting
confidence: 79%
“…4 ( 1.0 kcal/mol, is in relatively good agreement with the value D 298 (CF 3 -I) ) 54.3 ( 0.3 kcal/mol obtained by Asher and Ruscic, 6 which is in turn in excellent agreement with recent kinetic determinations by Skorobogatov et al [7][8][9] (54.4 4 ( 0.4 kcal/mol at 298 K) and in reasonable agreement with Kumaran et al 10 (55.6 ( 1.5 kcal/mol at 298 K). On the other hand, D 298 -(CF 3 -Br) ) 70.8 ( 0.3 kcal/mol, which was obtained by Asher and Ruscic 6 in a completely analogous fashion, is ∼1.4 kcal/ mol higher than the value of 69.4 ( 1.2 kcal/mol derived using JANAF's 1 ∆H f298°( CF 3 Br) ) -155.1 ( 0.7 kcal/mol while at the same time it is in exceedingly good agreement with the kinetic determinations by Tsang 4 and Skorobogatov et al 11,12 (70.5 ( 1.0 and 70.8 ( 0.2 kcal/mol, respectively) and has been additionally corroborated by the most recent measurements of Hranisavljevic et al 13 Hence, while it appears that these newer experiments achieve a consensus on the CF 3 -Br and CF 3 -I bond dissociation energies, they are at least partly at variance with JANAF's values.…”
Section: Introductionsupporting
confidence: 85%
“…The analogous applies to dissociation experiments for CF 3 Cl. [35] For the dissociation of CF 3 Br (see e. g. [35][36][37]), and even more that of CF 3 I, [27][28][29]35] the intermediate reaction order had to be accounted for. A representation as a first-order process here did not appear justified at all.…”
Section: Practical Problemsmentioning
confidence: 99%